2010
DOI: 10.4028/www.scientific.net/amr.93-94.202
|View full text |Cite
|
Sign up to set email alerts
|

Carrier Design for Astaxanthin Delivery

Abstract: Astaxanthin is a natural carotenoid pigment with powerful antioxidant capacity which has been reported for beneficial effects on human health to prevent cancers and anti-degenerative diseases. Bioavailability of astaxanthin is however limited due to insoluble and instable properties of its lipophilic nature. This study describes the cytotoxicity and astaxanthin delivery using a surfactant (tween 80) and penetration enhancers (methyl -cyclodextrin and liposome) to enhance astaxanthin bioavailability in human h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…The viability of Caco-2 cells exposed to both astaxanthin extract and liposomes was higher than 80%, indicating the absence of major cytotoxic effects. Similar results were obtained with astaxanthintreated HuH7, PON1-HuH7, and HepG2 cells (Cheeveewattanagul et al, 2010;Dose et al, 2016). Conversely, concentration-dependent toxicity of astaxanthin-tween 80 complex and astaxanthin-loaded methyl b-cyclodextrin was observed (Cheeveewattanagul et al, 2010).…”
Section: Morphological Characteristics Of Liposomessupporting
confidence: 80%
See 1 more Smart Citation
“…The viability of Caco-2 cells exposed to both astaxanthin extract and liposomes was higher than 80%, indicating the absence of major cytotoxic effects. Similar results were obtained with astaxanthintreated HuH7, PON1-HuH7, and HepG2 cells (Cheeveewattanagul et al, 2010;Dose et al, 2016). Conversely, concentration-dependent toxicity of astaxanthin-tween 80 complex and astaxanthin-loaded methyl b-cyclodextrin was observed (Cheeveewattanagul et al, 2010).…”
Section: Morphological Characteristics Of Liposomessupporting
confidence: 80%
“…Similar results were obtained with astaxanthintreated HuH7, PON1-HuH7, and HepG2 cells (Cheeveewattanagul et al, 2010;Dose et al, 2016). Conversely, concentration-dependent toxicity of astaxanthin-tween 80 complex and astaxanthin-loaded methyl b-cyclodextrin was observed (Cheeveewattanagul et al, 2010). Ribeiro et al (2006) measured the uptake by Caco-2 and HT-29 of astaxanthin and lycopene in oil-in-water emulsions prepared with a variety of emulsifiers: sucrose laurate, Tween 20, whey protein isolate, and hydrolyzed whey protein isolate.…”
Section: Morphological Characteristics Of Liposomessupporting
confidence: 57%
“…M-bCD was found to be the promising polymer for inclusion of LUT. Percent growth inhibition in LUT:M-bCD (1:2, SD), LUT:HP-bCD (1:2, SD) and LUT:bCD (1:2, SD) was found to be 1.92 times, 1.6 times and 1.5 times respectively more compared with plain LUT after 48 h of incubation at LUT concentration of 80 lg/mL [15].These results clearly demonstrate formation of inclusion complexes and thus increase in the cellular …”
Section: Srb Assaymentioning
confidence: 89%
“…CDs were used as solubilizing agent, simply mixed with carotenoids in different proportions [22,23,24,25]. Later it was found that carotenoids without cyclic end groups at least on one end (e.g., lycopene or bixin) could form 1:1 inclusion complexes which are more stable than the native carotenoids [26,27,28,29,30,31]. We have found that cyclic end-groups cannot enter the relatively apolar cavity of CDs because of their size, but 3-4 CD molecules surround each end-group and are bound there through secondary interactions.…”
Section: Complexation With Cyclodextrinsmentioning
confidence: 99%